Inhibitory potential of Japanese papaya (Cnidoscolus aconitifolius) leaf juice against the growth of Escherichia coli - Hijriani, Baiq Isti; Solihin, Solihin; Kurniawan, Edy; Atfal, Bustanul (JSN : Jurnal Sains Natural, 2025)
Indonesia is a country with high biodiversity that have many plants, one of them is japanesse pepaya plant (Cnidoscolus aconitifolius). Japanese pepaya leaves used by people as a traditional medicine, this is because pepaya leaves contain compounds that can act as antibacterials. Escherichia coli is a normal flora that found in the human large intestine (colon). Escherichia coli can cause primary infections, one of the infections is diarrhea. The purpose of this study was to determine the ability of Japanese pepaya leaf juice (Cnidoscolus aconitifolius) to inhibit the growth of Escherichia coli bacteria and to determine the concentration of Japanese pepaya leaf extract that is effective in inhibiting the growth of Escherichia coli bacteria. This type of research is a laboratory experiment. The inhibition test used the Kirby Bauer agar diffusion method. The research variables were the concentration of Japanese pepaya leaf extract of 25%, 50%, 75%, and 100%, and the growth inhibition zone of Escherichia coli bacteria. The results of this study showed that no inhibition zone formed around the wells when Japanese pepaya extract was administered at various concentrations. The conclusion of this study is that Japanese pepaya (Cnidoscolus aconitifolius) leaf juice has no potential to inhibit the growth of Escherichia coli bacteria.